En akademisk trettioårskris? Om rutiniseringen av Cultural Studies - Löfgren, Orvar (Kulturella Perspektiv – Svensk etnologisk tidskrift, 1994)
During its thirty year history Cultural Studies has developed from an interdisciplinary meeting ground and a "street-urchin of Academia" to a discipline, with its own traditions and routines. Such a process often involves a rather unconscious framing of research and teaching — a tendency to overlook some aspects and to overexploit others. The paper takes a critical look at this transformation, especially at the way in which interests in "everyday life" has been narrowed down considerably. Latterly, too much research in Cultural Studies has tended to favour a "reading of culture", focusing on the symbolic and expressive aspects of consumption, as well as the aesthetic dimensions of creativity.